Unraveling the phylogeny of Chaetopteridae (Annelida) through mitochondrial genome analysis - Wu, Xiu; Su, Xuechun; Wang, Yu; He, Caifang; Qiu, Jian-Wen; Zhang, Yanjie (Frontiers in Marine Science, 2024)
Mitochondrial genomes serve as valuable markers for phylogenetic and evolutionary studies across diverse invertebrate taxa, but their application within Annelida remains limited. In this study, we report the mitochondrial genomes of seven species from four genera of Chaetopteridae (Annelida), obtained by high-throughput sequencing. Phylogenetic analysis was performed using cox1, 18S, 28S and all mitochondrial genes. Our results reveal Chaetopterus and Mesochaetopterus as wellsupported monophyletic sister clades, while Phyllochaetopterus and Spiochaetopterus appear paraphyletic, with species from both genera in a mixed clade sister to Chaetopterus + Mesochaetopterus. While mitochondrial gene orders remain conserved within Chaetopteridae, they appear substantially different from those of the ancestral patterns in Annelida. All 13 protein-coding genes found in Chaetopteridae evolved under strong purification selection, although Phyllochaetopterus exhibited the highest base-substitution rate for most of them, suggesting a more relaxed purified selection. Overall, our study provides molecular resources for phylogenetic studies of Chaetopteridae, highlighting the necessity for a comprehensive revision of the family, particularly dealing with the paraphyletic Phyllochaetopterus and Spiochaetopterus.